Risk Perception of Small Islands Community on Climate Change: Evidence From Mepar and Baran Islands, Indonesia - Tezar Tezar; Rukuh Setiadi (Island Studies Journal)
This study explores climate risk perception of communities in two small islands, Mepar and Baran, located in Lingga Regency, Riau Islands Province to fill in the lack of knowledge regarding the topic in Indonesia and to support island bottom-up climate change adaptation planning. This study uses proportional random sampling and a questionnaire survey of 165 households to collect data related to demography, level of knowledge, level of risk perception, and adaptation actions taken by communities. We use descriptive statistics and employ discriminant analysis to determine factors influencing risk perception of these small islands' communities. We identify two categories of risk perception in this study as a basis for analysis, namely risk perception on climate change hazards and climate change risk perception on community's life. This study finds four factors that consistently influence both types of risk perception on climate change. These are the number of climate change indicators perceived, age, and the experience on extreme weather both at sea and on the island. Other influencing factors which have a partial role include the duration of residence on the island, place of birth, education level, and trade relations. We then critically discuss the results within the complexity of small island development and bottom-up climate change adaptation.